Natural gas generation in the deep-water area of the Qiongdongnan Basin, China. (17th December 2018) - Su, Long; Zhang, Dongwei; Liu, Peng; Chen, Ying; Lin, Jihui
Abstract: Generation process of natural gas in the Yacheng formation, including mudstone and coal strata, is simulated by an open system laboratory pyrolysis apparatus. The results show that higher geothermal gradient of the central depression could accelerate the generation of methane in the deep-water sags and the transformation of the residual hydrocarbons to methane in the deep-water area began from 5.3 Ma. Therefore, the main sags in the deep-water area are of high gas generation potential.